Estrous Cycle-dependent Morphology in the Reproductive Organs of the Female Göttingen Minipig. (December 2014) - de Rijk, Eveline; van den Brink, Hetty; Lensen, Joost; Lambregts, Ankie; Lorentsen, Helle; Peter, Birgit
The present study describes the normal histology of female reproductive organs during the estrous cycle in the Göttingen minipig. For this purpose, sexually mature females were sacrificed at different phases of the cycle (follicular/proliferation, ovulation, and early-, mid-, and late-luteal/secretory phase). Ovaries, uterus, cervix, vagina, and mammary gland tissues were processed for microscopic evaluation. Sexual maturity was assured by selecting females in which at least 1 progesterone peak was measured. Stage-distinguishing features in ovaries were the Graafian follicles (disrupted vs. nondisrupted) and corpora lutea of recent and preceding cycles (size, cell morphology, and structural composition). In the uterus, stage-specific markers were epithelial morphology, secretory activity (using periodic acid–Schiff/hematoxylin staining), and epithelial mitosis and/or apoptosis. The other reproductive organs were not suitable to discriminate between the different phases of the cycle due to a high morphologic variability (mammary gland, and vagina) or absence of clear morphologic differences between the phases (cervix). The increased use of young minipigs (frequently immature/peripubertal) in preclinical testing requires more knowledge on the histologic cyclic changes. With the present morphologic description of the morphologic characteristics of the reproductive tract in recently ovulating minipigs, a guidance for staging the estrous cycle and determination of sexual immaturity is provided.